2018
DOI: 10.1016/j.dsr2.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of iron in sediments from the Sea of Marmara

Abstract: Two ~1000 cm long sediment cores were recovered from the Sea of Marmara, one with the occurrence of gas hydrates in the Western High, and the other without hydrates in the Cinarcik Basin. Differences in mineralogical and chemical compositions have been identified between the two sediment cores. Based on the results of the mineralogical and geochemical analyses, the main sources of the sediments are quite similar for both investigated areas, but the authigenic components are different, particularly iron sulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…However, the high-resolution multi-proxy study carried out by Teichert et al (2018) provides a promising example of the use of authigenic carbonates as archives of past seismic activity. Iron has also been investigated as proxy for tracing the migration of fluids within the sedimentary column and their discharge at the seafloor (Yang et al, 2018). The presence of metastable ferromagnetic iron sulfide minerals on the Western High indicates a more reducing environment resulting from the degradation of heavy hydrocarbons and organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high-resolution multi-proxy study carried out by Teichert et al (2018) provides a promising example of the use of authigenic carbonates as archives of past seismic activity. Iron has also been investigated as proxy for tracing the migration of fluids within the sedimentary column and their discharge at the seafloor (Yang et al, 2018). The presence of metastable ferromagnetic iron sulfide minerals on the Western High indicates a more reducing environment resulting from the degradation of heavy hydrocarbons and organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to Cr being available only in trace amounts in the Durban Harbour sediments, thus leading to minimal accumulation in pellets. While iron is found in high background concentrations in sediments, it is also one of the key reactive elements in marine sediments and is highly subject to phase transformations by redox processes [26,27], which may impair its rate of accumulation on pellets. Holmes, Turner, and Thompson [13] similarly found metal concentration to be higher in pellets than in sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have revealed that pH is a critical factor influencing the carbonate saturation state in sediments, with low pH leading to the dissolution of carbonates (Waldbusser et al, ). In the Western High, the sedimentary environment with low pH is created by anaerobic biodegradation of seeping petroleum, a phenomenon recognized by the occurrence of greigite (Yang et al, ). Greigite is formed in anoxic environments with a pH less than 5 (Roberts & Weaver, ), where carbonates, and primarily foraminifera, are dissolved.…”
Section: Discussionmentioning
confidence: 99%
“…The upper 0–79 cm below seafloor (cmbsf) part of the marine unit is dark green gray silty clay. This portion has a porous, brecciated structure resulting from gas hydrate dissociation and a strong smell of H 2 S. The lower part of the unit between 79 and 305 cmbsf is a sapropel containing up to 1.8 wt.% total organic carbon (TOC), which is clearly higher than that of 1.2 wt.% for the lacustrine unit below (Yang et al, ; Figure a). This sapropel layer (305–316 cmbsf) corresponds to the Holocene sapropel layer previously described in the SoM (Çağatay et al, ; Çağatay et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation